Indels ascertain the phylogenetic position of Coleodactylus elizae Gonçalves, Torquato, Skuk & Sena, 2012 (Gekkota: Sphaerodactylidae) - Correia, Larissa Lima; Gamble, Tony; Landell, Melissa Fontes; Mott, Tamí (Zootaxa, 2016)
The Neotropical gecko genus Coleodactylus Parker 1926 was, until recently, composed of five species: C. amazonicus (Andersson 1918), C. brachystoma (Amaral 1935), C. meridionalis (Boulenger 1888), C. natalensis Freire 1999, and C. septentrionalis Vanzolini 1980 (Geurgas et al. 2008). However, several phylogenetic analyses recovered a polyphyletic Coleodactylus (Geurgas et al. 2008; Gamble et al. 2011a) leading Gamble et al. (2011b) to recognize a new genus, Chatogekko, for C. amazonicus. Coleodactylus and Chatogekko differ in both morphological and molecular characters. Coleodactylus has smooth dorsal scales and five scales forming the ungual sheath, while Chatogekko has keeled dorsal scales and four scales forming the ungual sheath (Gamble et al. 2011b). Furthermore, all Coleodactylus species have two deletions in the protein coding recombination-activating gene 1 (RAG1), one of six base pairs (bp) and another of 18 bp (Gamble et al. 2008a; Geurgas et al. 2008), while Chatogekko has a unique three bp deletion in the RBMX gene and a three bp deletion in the protein tyrosine phosphatase nonreceptor type 12 gene (PTPN12) (Gamble et al. 2011b). In addition, Chatogekko is differentiated from all others geckos by a unique set of 10 craniofacial features (Gamble et al. 2011b).